Sièm Occitans en prumièr o […] sièm pas ren du tot : une allocution d’Yves Rouquette (2009). Édition d’extraits, avec une introduction, des notes et une étude des diatopismes remarquables - Jean-Pierre Chambon; Marjolaine Raguin-Barthelmebs; Jean Thomas (Revue des Langues Romanes)
This contribution aims to give a philologically correct edition of extracts from an Occitan contemporary oral text which makes sense for the history of Occitan literature and the Renaissance movement. The speaker is the great Occitan writer Yves Rouquette (1936-2015). The treatment of the document strives to satisfy the editorial requirements most often reserved to Occitan medieval literary texts: a presentation of the speech and its context, an elaboration of editing criteria adapted to the document, an establishment of the text in the orthography used by Yves Rouquette in his literary work, a critical apparatus of a particular type (giving an account of the speaker's gestures, of some phonetic and phonostylistic realizations, speech misses, etc.), explanatory notes interpreting in detail the meaning of the text, a translation, and a study of the most local features of the speaker's Occitan variety (identifiable with that of Camarès, Aveyron).